An Interview with Mr. Moti Lal Dugar - Dugar, Moti Lal (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
In light of ongoing discourses, at present, on prevailing energy crisis and exciting participation of IPPs in hydropower development in Nepal, HYDRO Nepal Journal felt this opportune to review and assess the present hydropower development scenario of Nepal from the perspective of independent power producer. Hence, HYDRO Nepal takes pleasure in presenting an interview with Mr. Moti Lal Dugar, Chairman of MV Dugar Group, Nepal by Rajendra P Thanju, Managing Editor of HYDRO Nepal Journal. HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue No: 22Page: 51-52Uploaded date: January 14, 2018